235k views
2 votes
Solve 5c 4 = -26
a. 6
b. -6
c. -4.4
d. 3

User Ryun
by
7.8k points

1 Answer

5 votes
Simplifying 5C + -4 + -2C + 1 = 8C + 2 Reorder the terms: -4 + 1 + 5C + -2C = 8C + 2 Combine like terms: -4 + 1 = -3 -3 + 5C + -2C = 8C + 2 Combine like terms: 5C + -2C = 3C -3 + 3C = 8C + 2 Reorder the terms: -3 + 3C = 2 + 8C Solving -3 + 3C = 2 + 8C Solving for variable 'C'. Move all terms containing C to the left, all other terms to the right. Add '-8C' to each side of the equation. -3 + 3C + -8C = 2 + 8C + -8C Combine like terms: 3C + -8C = -5C-3 + -5C = 2 + 8C + -8C Combine like terms: 8C + -8C = 0 -3 + -5C = 2 + 0 -3 + -5C = 2 Add '3' to each side of the equation. -3 + 3 + -5C = 2 + 3 Combine like terms: -3 + 3 = 0 0 + -5C = 2 + 3 -5C = 2 + 3 Combine like terms: 2 + 3 = 5 -5C = 5 Divide each side by '-5'. C = -1 Simplifying C = -1
User Alpesh Jikadra
by
8.3k points